Early Development of Quranic Exegesis in Malaysia - Hussin, Haziyah; Majid, Latifah Abdul (International Journal of Asian Social Science, 2013)
According to Syed Naquib al-Attas and Mahayudin Yahaya, the teaching of Islam arrived in Malaysia during the end of 9th century, though historical notes on the study and writing of Quranic exegesis or tafsir were not much found except after the 20thcentury. Besides, reviewing the literature on the topic found that the writings do not describe the tafsir development in-depth as well factors due to it. The study therefore, aims to analyze the early stages of tafsir development inthe country, also determine factors affected it. Research methods used to examine the exegesis of Quranic studies are largely qualitative, and consist of approaches such as historical research and content analyses. Therefore in the interests of validity and reliability, the study provides multiple sources of evidence. These include tape-recorded in-depth interviews with specific researches in particular with an expert educationalist and academician’s affairs in Malaysia. As a result, based on the discussion, the present article affirms that the earliest developments of tafsir studies were taught to the Malay region simultaneously with the coming of Islam. This is mainly because there are two main sources for an understanding of Islam; the Holy Qur’an and the Hadith. Regards, it has been developed onwards, thus, influenced by two main streams or tendencies; Madrasah Muhammad Abduh and of Sheikh Waliyullah al-Dihlawi. The influence of Muhammad Abduh and his disciples, Rashid Rida and al-Maraghi for example, was very significant to the local scholars who were educated in the Middle East, thereby contributing to the development of tafsir writing in the country.